Pengaruh model pembelajaran game based learning terhadap minat belajar siswa pada pembelajaran pendidikan Pancasila kelas V di SD Negeri Gugus V Tempel Sleman - Hidayat, Taufiq; Nadziroh, Nadziroh; Nugroho, Irfan Adi; Kemala, Vinna Dinda (Universitas Sarjanawiyata Tamansiswa, 2025)
This study has two objectives, the first of which is to describe the effect of the game-based learning model on students' learning interest in Pancasila Education learning for grade V at SD Negeri Gugus V Tempel Sleman. The second study aims to comparatively test the differences in students' learning interests between classes that use the game-based learning model and the problem-based learning model. This type of research is a quantitative experiment. This study used two classes, namely the experimental class and the control class. The experimental class was treated with the game-based learning model, while the control class was treated using the project-based learning model. The population in this study was all grade V students of SD Negeri Banyurejo 2, totaling 18 students, and all grade V students of SD Negeri Banyurejo 4, totaling 16 students; the total population of this study was 34 students. The sampling technique in this study is saturated sampling which can be interpreted as meaning that all populations are sampled. The data collection technique uses questionnaires, documentation, and instruments to obtain data on students' interest in learning Pancasila Education. Pre-tests and post-tests are given to determine the condition of students' interest in learning before and after being given treatment. The results of this study are descriptive (1). Interest in learning Pancasila Education in class V of SD Negeri Banyurejo 2 which uses the game-based learning model, is in the very high category with an average score of 85.94. (2) The interest in learning Pancasila Education of class V of SD Negeri Banyurejo 4, which uses the project-based learning model, is in the high category with an average score of 78.44. Comparatively, there is a significant difference between classes using the game-based learning model and project-based learning with a t-test of 6.579 and a p-value of 0.000. The average interest in learning using the game-based learning model is higher, so it can be concluded that there is a difference in the influence of the application of the game-based learning model on the interest in learning Pancasila Education of class V of SD Negeri Gugus V Tempel Sleman.